Using talk to support writing - Fisher, Ros.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
This text presents an approach to the teaching of early writing. It discusses both theoretical and practical issues around using talk in the classroom to support children as they learn to write.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: English language -- Composition and exercises -- Study and teaching (Elementary) -- Great Britain; Children -- Language; Oral communication; Electronic books